A Machine Learning Approach for the Differential Diagnosis of Alzheimer and Vascular Dementia Fed by MRI Selected Features - Castellazzi, Gloria; Cuzzoni, Maria Giovanna; Cotta Ramusino, Matteo; Martinelli, Daniele; Denaro, Federica; Ricciardi, Antonio; Vitali, Paolo; Anzalone, Nicoletta; Bernini, Sara; Palesi, Fulvia; Sinforiani, Elena; Costa, Alfredo; et al. (Frontiers in Neuroinformatics, 2020)
Among dementia-like diseases, Alzheimer disease (AD) and Vascular Dementia (VD) are two of the most frequent. AD and VD may share multiple neurological symptoms that may lead to controversial diagnoses when using conventional clinical and MRI criteria. Therefore, other approaches are needed to overcome this issue. Machine learning (ML) combined with magnetic resonance imaging (MRI) has been shown to improve diagnostic accuracy of several neurodegenerative diseases, including dementia. To this end, in this study we investigated, first, whether different kind of ML algorithms, combined with advanced MRI features, could be supportive in classifying VD from AD; secondly, whether the developed approach might help in predicting the prevalent disease in subjects with an unclear profile of AD or VD. Three ML categories of algorithms were tested: artificial Neural Network (ANN), support vector machine (SVM), and Adaptive Neuro-Fuzzy Inference System (ANFIS). Multiple regional metrics from resting-state fMRI (rs-fMRI) and Diffusion Tensor Imaging (DTI) of 60 subjects (33 AD, 27 VD) were used as input features to train the algorithms and find the best feature pattern to classify VD from AD. We then used the identified VD-AD discriminant feature pattern as input for the most performant ML algorithm to predict the disease prevalence in 15 dementia patients with a “mixed VD-AD dementia” (MXD) clinical profile using their baseline MRI data. ML predictions were compared with the diagnosis evidence from a three years clinical follow-up. ANFIS emerged as the most efficient algorithm in discriminating AD from VD reaching a classification accuracy greater than 84% using a small feature pattern. Moreover, ANFIS showed improved classification accuracy when trained with a multimodal input feature dataset (e.g. DTI + rs-fMRI metrics) rather than a unimodal feature dataset. When applying the best discriminant pattern to the MXD group, ANFIS achieved a correct prediction rate of 77.33%. Overall, results showed that our approach have a high discriminant power to classify AD and VD profiles. Moreover, the same approach showed also potential in predicting earlier the prevalent underlying disease in dementia patients whose clinical profile is uncertain between AD and VD, therefore suggesting its usefulness in supporting physicians’ diagnostic evaluations.